PENGARUH KEDISIPLINAN GURU MENGAJAR TERHADAP PENINGKATAN MOTIVASI DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN AQIDAH AKHLAK DI MIN 1 KOTA BENGKULU - Siti Maruya (IAIN Bengkulu, 2016)
This research aims to know: (1) students’ system in a lesson in morals aqidah MIN 1 Bengkulu City? and (2) whether the teacher teaches discipline may influence towards improving student learning outcomes in the belief moral lesson in MIN 1 Bengkulu City. This type of research is classified as a field research (field research), using a quantitative approach that the data in the form of figures relating to the research theme. To determine the influence of teachers teaching discipline to increased motivation and student learning outcomes in learning Aqidah Morals at MIN 1 Bengkulu city, the authors analyzed using quantitative methods that the formula used is product moment.Based on the data processing and discussion of the results in the previous chapter, it can be concluded that: (1) The level of discipline teachers Aqidah Morals in MI country 1 Tanjung Agung is on. category